Vitamin B12 metabolism in Mycobacterium tuberculosis. (November 2013) - Gopinath, Krishnamoorthy; Moosa, Atica; Mizrahi, Valerie; Warner, Digby F
Mycobacterium tuberculosis is included among a select group of bacteria possessing the capacity for de novo biosynthesis of vitamin B12, the largest and most complex natural organometallic cofactor. The bacillus is also able to scavenge B12 and related corrinoids utilizing an ATP-binding cassette-type protein that is distinct from the only known bacterial B12 -specific transporter, BtuFCD. Consistent with the inferred requirement for vitamin B12 for metabolic function, the M. tuberculosis genome encodes two B12 riboswitches and three B12 -dependent enzymes. Two of these enzymes have been shown to operate in methionine biosynthesis (MetH) and propionate utilization (MutAB), while the function of the putative nrdZ -encoded ribonucleotide reductase remains unknown. Taken together, these observations suggest that M. tuberculosis has the capacity to regulate core metabolic functions according to B12 availability – whether acquired via endogenous synthesis or through uptake from the host environment – and, therefore, imply that there is a role for vitamin B12 in pathogenesis, which remains poorly understood.